Systematic literature review on microtakaful and women entrepreneurship. - Rosman, Romzie; Mohd Yusoff, Syarah Syahira; Kassim, Salina; Muhammad Nasir, Nur I’ffah; Zamzamir@Zamzamin, Zaminor (Human Resource Management Academic Research Society, 2024)
Microtakaful does not mirror the concept of microinsurance. It is rooted in Islamic principles of mutual aids, such as Tabarru (voluntary contribution), Taawun (cooperation), and avoiding Riba (interest). The goal of microtakaful is to assist the underprivileged group to protect their future financial well being. This investigation focuses on how microtakaful applies to women entrepreneurs, a group often overlooked in the realm of financial risk management studies. With its unique aim, structure, risk protection, affordability, and selection criteria, microtakaful aims to bolster the economic resilience of less privileged individuals, particularly women who start and operate their own businesses. The limited research at the juncture of microtakaful and women's entrepreneurship points to a substantial void in scholarly work. Tackling this omission, the current study evaluates existing publications sourced from databases like Scopus and Google Scholar and key scholarly journals. By examining these articles, the study pinpoints various key themes and documents how microtakaful could significantly support women business owners, providing vital information for parties interested in promoting women's roles in commerce.